Quality Improvement Project to Change Prescribing Habits of Surgeons from Combination Opioids Such as Hydrocodone/Acetaminophen to Single-Agent Opioids Such as Oxycodone in Pediatric Postop Pain Management - Muhammad Aishat; Alicia Segovia; Throy Campbell; Lorrainea Williams; Kristy Reyes; Tyler Hamby; David Farbo; Meredith Rockeymoore Brooks; Artee Gandhi (Anesthesia Research)
Background: While multimodal analgesia is the standard of care for postoperative pain relief, opioid medications continue to be a part of the treatment regimen, especially for more invasive surgeries such as spinal fusion, craniofacial reconstruction, laparotomy, and others. In pediatric patients, safe usage, storage, and dosing are especially important, along with clear instructions to caregivers on how to manage their child’s pain. Combination opioids such as hydrocodone with acetaminophen and acetaminophen with codeine are the most commonly prescribed opioid medications for postoperative pain control. However, these combination products can lead to acetaminophen toxicity, limit the ability to prescribe acetaminophen or ibuprofen, and add to caregiver confusion. Administering acetaminophen and ibuprofen individually rather than in combination products allows the maximal dosing of these nonopioid medications. The primary aim of this quality improvement (QI) project was to increase the utilization of single-agent opioids for postoperative pain control, primarily oxycodone, by the various surgical groups here at Cook Children’s Medical Center (CCMC). Methods: The project setting was a tertiary-level children’s hospital with a level 2 trauma center, performing over 20,000 surgeries annually. The opioid stewardship committee (OSC) mapped the steps and overlapping activities in the intervention that led to changes in providers’ prescription practices. A Plan–Do–Study–Act continuous improvement cycle allowed for an assessment and modification of implementation strategies. Statistical control process charts were used to detect the average percentage change in surgical specialties using single-agent opioid therapy. Data were monitored for three periods: one-year pre-intervention, one-year post-intervention, and one-year sustainment periods. Results: There were 4885 (41%) pre-intervention procedures, 3973 (33%) post-intervention procedures, and 3180 (26%) sustainment period procedures that received opioids. During the pre-intervention period, the average proportion of single-agent opioids prescribed was 8%. This average shifted to 89% for the first five months of the post-intervention period, then to 91% for the remainder of the study. Conclusions: The methodical application of process improvement strategies can result in a sustained change from outpatient post-surgical combination opioid prescriptions to single-agent opioid prescriptions in multiple surgical departments.